Association between daytime nap duration and risks of frailty: Findings from the China Health and Retirement Longitudinal Study - Zhang, Yan; Zhou, Lixing; Ge, Meiling; Lin, Xiufang; Dong, Birong (Frontiers in Public Health, 2023)
Introduction: Night sleep duration and total sleep duration are associated with frailty. However, the association between daytime nap duration and risks of frailty has not been thoroughly explored. Methods: This study used data from the China Health and Retirement Longitudinal Study. Participants aged 60 years and older at baseline were included in this study. Daytime nap duration was categorized into four groups: no napping, short napping (<30 minutes), moderate napping (30–89 minutes), and extended napping (≥90 minutes). Frailty was assessed using a modified physical frailty phenotype scale. Nonfrail participants at baseline were followed up for four years. The associations between nap duration and frailty at baseline and incident frailty were evaluated by logistic regression and discrete-time Cox regression analyses, respectively. Results: In total, 5126 participants were included in this study. For individuals with ≥9 hours night sleep duration, short nappers showed higher odds (OR= 4.08, 95% CI: 1.30–12.78) for frailty compared with non-habitual nappers at baseline, while moderate nappers were less likely to be frail (OR= 0.18, 95% CI: 0.04–0.73). In the follow-up study, short nap duration was associated with higher risks for frailty compared with no napping for participants with night sleep duration <6 hours (HR= 1.91; 95% CI: 1.07–3.43) or 6 to 9 hours (HR=1.97; 95% CI: 1.18–3.30). Compared with short nappers, older adults with extended napping (HR= 0.41; 95% CI: 0.22–0.77) showed lower risks for frailty in those with night sleep duration of 6 to 9 hours. For individuals with ≥9 hours night sleep, moderate napping (HR= 0.20; 95% CI: 0.05–0.77) decreased risks for frailty compared with short napping. Conclusion: For older adults with night sleep duration <9 hours, short nappers posed higher risks for frailty compared with non-habitual nappers. Extended naps for those with night sleep duration of 6 to 9 hours or moderate naps for those with ≥9 hours night sleep duration could lower the risks of frailty compared with short naps. Future studies regarding the timing, purpose, frequency and quality of daytime napping and objectively measured nap duration are needed to explore the association of daytime napping and risks of frailty.